The contribution of prenatal environment and genetic factors to the association between birth weight and adult grip strength. - Charlotte L Ridgway; Stephen J Sharp; Catherine Derom; Gaston Beunen; Robert Fagard; Robert Vlietinck; Ulf Ekelund; Ruth J F Loos (PLoS ONE)
Low birth weight has been associated with reduced hand grip strength, which is a marker of future physical function and disease risk. The aim of this study was to apply a twin pair approach, using both 'individual' data and 'within-pair' differences, to investigate the influence of birth weight on hand grip strength and whether this association may be mediated through fat free mass (FFM). Participants from the East Flanders Prospective Twin Survey were included if born without congenital abnormalities, birth weight >500 g and ≥22 weeks of gestation. Follow up in adulthood (age: 18-34 year), included anthropometric measures and hand grip (n = 783 individuals, n = 326 same-sex twin pairs). Birth weight was positively associated with hand grip strength (β = 2.60 kg, 95% CI 1.52, 3.67, p<0.001) and FFM (β = 4.2, 95% CI 3.16, 5.24, p<0.001), adjusted for gestational age, sex and adult age. Using 'within-pair' analyses, the birth weight hand grip association was significant in DZ men only (β = 5.82, 95% CI 0.67, 10.97, p = 0.028), which was attenuated following adjustment for FFM. Within-pair birth weight FFM associations were most pronounced in DZ men (β = 11.20, 95% CI 7.18, 15.22, p<0.001). Our 'individual' analyses show that higher birth weight is associated with greater adult hand grip strength, which is mediated through greater adult FFM. The 'within-pair' analyses confirm this observation and furthermore show that, particularly in men, genetic factors may in part explain this association, as birth weight differences in DZ men result in greater differences in adult strength and FFM.